IV BCG Vaccination and Aerosol BCG Revaccination Induce Mycobacteria-Responsive γδ T Cells Associated with Protective Efficacy against M. tb Challenge - Alexandra L. Morrison; Charlotte Sarfas; Laura Sibley; Jessica Williams; Adam Mabbutt; Mike J. Dennis; Steve Lawrence; Andrew D. White; Mark Bodman-Smith; Sally A. Sharpe (Vaccines, 2023)
Intravenously (IV) delivered BCG provides superior tuberculosis (TB) protection compared with the intradermal (ID) route in non-human primates (NHPs). We examined how γδ T cell responses changed in vivo after IV BCG vaccination of NHPs, and whether these correlated with protection against aerosol M. tuberculosis challenge. In the circulation, Vδ2 T cell populations expanded after IV BCG vaccination, from a median of 1.5% (range: 0.8–2.3) of the CD3+ population at baseline, to 5.3% (range: 1.4–29.5) 4 weeks after M. tb, and were associated with TB protection. This protection was related to effector and central memory profiles; homing markers; and production of IFN-γ, TNF-α and granulysin. In comparison, Vδ2 cells did not expand after ID BCG, but underwent phenotypic and functional changes. When Vδ2 responses in bronchoalveolar lavage (BAL) samples were compared between routes, IV BCG vaccination resulted in highly functional mucosal Vδ2 cells, whereas ID BCG did not. We sought to explore whether an aerosol BCG boost following ID BCG vaccination could induce a γδ profile comparable to that induced with IV BCG. We found evidence that the aerosol BCG boost induced significant changes in the Vδ2 phenotype and function in cells isolated from the BAL. These results indicate that Vδ2 population frequency, activation and function are characteristic features of responses induced with IV BCG, and the translation of responses from the circulation to the site of infection could be a limiting factor in the response induced following ID BCG. An aerosol boost was able to localise activated Vδ2 populations at the mucosal surfaces of the lung. This vaccine strategy warrants further investigation to boost the waning human ID BCG response.